Computational Study on the Hemodynamic Analysis of Intracranial Aneurysms using Flow Diverter Stents - Syukri Arafat, Muhammad Affiq; Nor Salim, Nor Adrian; Mohd Syahar Mohd Shawal,; Mohd Rosdzimin Abdul Rahman, (International Journal of Integrated Engineering, 2025)
Intracranial aneurysms represent a critical cerebrovascular pathology with a high risk of rupture-induced subarachnoid haemorrhage, necessitating effective endovascular interventions such as flow diverter (FD) stents to reconstruct the parent vessel and induce curative thrombosis. However, the therapeutic efficacy of these devices varies significantly based on their geometric configuration, requiring precise analysis of the hemodynamic alterations they induce within the aneurysm sac. This study aims to perform a comprehensive computational fluid dynamics (CFD) investigation to quantify changes in velocity, time-averaged wall shear stress (TAWSS), oscillatory shear index (OSI), and relative residence time (RRT) following the virtual deployment of five distinct FD stent designs. Using ANSYS Fluent 2023, transient simulations were conducted on an idealized saccular aneurysm model under pulsatile physiological conditions, treating blood as an incompressible Newtonian fluid to compare a baseline untreated model against five stented configurations (Models 2–6). The quantitative results demonstrated that stent geometry critically influences flow diversion; specifically, Model 6 exhibited the most superior performance by achieving near-complete flow stagnation with velocity and pressure reductions exceeding 90% compared to the untreated baseline velocity of 0.39  0.04 m/s, and Model 3 achieved a beneficial 5.54% reduction in WSS, whereas Model 5 proved suboptimal with a 2.77% increase in WSS and unfavourable residence time characteristics. In conclusion, the study confirms that optimizing stent design parameters is essential for establishing the low-flow, high-residence-time environment required for successful aneurysm occlusion, thereby validating CFD as a vital predictive tool for enhancing FD treatment strategies.